Office Administration Technology Skill of Vocational School on the 21st Century - Hanisa Sismaya Lestari; Mia Aulia (Universitas Sebelas Maret, 2018)
In the 21st century education becomes more important to ensure students have the life skills and careers, learning and skills Databank as well as expertise in information technology and the media. Information technology is developing rapidly in a wide range of areas, including administrative services office. Records management is one of the activities of the Office of administrative services in a wide range of new. Vocational schools are required to generate human resources have the skills to use information technology. Electronic archive of educational practice to become one of the basic competencies taught in vocational schools in Office administration skills. Competencies expected to produce human resource who are competent and ready to compete in a globalized world. This method is used in this research is descriptive in the tests. The quality of education of a country can be seen from the data of the human development index (HDI) liquid size comparison of life expectancy, literacy, education and reduce the standard of living for all countries around the world. HDI data results in the year 2015 shows that Indonesia is number 35 with 70.1 rating from 41 countries around the world. This shows that the quality of education in Indonesia is still low compared with other countries.